Natural killer cells as COVID-19 therapy - Kennedy, Philippa (Henry Stewart Talks, 2020)
The role of Natural Killer (NK) cells in viral infections, Why NK cells are being investigated, Induced pluripotent stem cell derived natural killer cells for SARS-CoV-2 therapy, Benefits of this therapy, Current stage of the clinical trial